HUBUNGAN ANTARA KOMPONEN RUMAH DAN JARAK RUMAH TERHADAP KADAR SO¬2 DALAM RUMAH DI SEKITAR TEMPAT PEMBUANGAN AKHIR SAMPAH (TPA) NAMO BINTANG KECAMATAN PANCUR BATU KABUPATEN DELI SERDANG TAHUN 2012 - Shinta Dewi Putri Sinaga; wirsal hasan; surya dharma (Lingkungan dan Kesehatan Kerja, 2013)
Relationship between the component of the house and the distance between house of SO2 in the house around Namo Bintang final disposal waste Pancur Batu distric Deli Serdang regency in 2012. Final disposal waste has a very important function, but it potentially caused environment degradations. It is caused by a pile of garbage producing a variety of pollutans that could cause air pollution such as SO2 (Sulfur dioxide), either inside or out side the house around landfill side.This research was an analytic survey with a cross-sectional study design and the population was entire houses locating in Dusun III Desa Baru. The sample size taken was 32 houses, drawn by simple random sampling method.The aim of this study was determine the relationship between the component of the house, and the distance between house of SO2 in the house.The results showed that there wasn’t relationship between the components that include ceiling, windows home, family and guest room windows, vents, and disposal facilities kitchen smoke while SO2 levels, with p value = 0,848; 0,234; 0,081; 0,792; and 0,206. Construction of the walls of the house showed was relationship with SO2 levels, with p =0,034. There was no relationship between the distance between home and SO2 levels with p = 0,994. For that, it is needed an attention of the public and government to increase public knowledge about the components of a qualified home through health promotion and improvement of the components in order to avoid air pollution. Keywords : components home, distance, SO2 (Sulfur dioxide)